2011
DOI: 10.1259/bjr/24318075
|View full text |Cite
|
Sign up to set email alerts
|

Unusual manifestation of endometrioid adenocarcinoma arising from subserosal cystic adenomyosis of the uterus: emphasis on MRI and positron emission tomography CT findings

Abstract: ABSTRACT. There are several reports of adenocarcinoma developing within adenomyosis of the uterus, but imaging features of MRI, including diffusion-weighted imaging (DWI) and positron emission tomography (PET)-CT, have not been published. Herein we report a rare case of endometrioid adenocarcinoma arising from subserosal cystic adenomyosis to emphasise the unusual growth features, as well as the imaging findings of the tumour on MRI and PET-CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The incidence of adenomyosis in women with endometrioid adenocarcinoma ranges between 10 and 70% [71]. The exact prevalence is difficult to determine because of the relatively small case series available and because of the lack of consistency in diagnosing adenomyosis [113].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of adenomyosis in women with endometrioid adenocarcinoma ranges between 10 and 70% [71]. The exact prevalence is difficult to determine because of the relatively small case series available and because of the lack of consistency in diagnosing adenomyosis [113].…”
Section: Resultsmentioning
confidence: 99%
“…Other rare malignancies identified in adenomyosis or its variants include adenosarcoma [70] and endometrioid adenocarcinoma arising from subserosal cystic adenomyosis [65, 71]. The exact number of cases reported in literature is difficult to determine as classification of many of the cases has been disputed, but considering the authors’ original classification, the total number of cases of malignancy originating in adenomyosis is in the region of 78 cases.…”
Section: Endometrial Cancer Arising Within Adenomyotic Focimentioning
confidence: 99%
“…However, solid areas of the mass were clearly enhanced on gadolinium-enhanced T1weighted images in our case as well as in the case of previously reported endometrioid adenocarcinoma arising from cystic adenomyosis. 11 These facts indicate that MRI with contrast enhancement will be useful for detecting the malignant transformation of the intrauterine cystic lesions.…”
Section: Discussionmentioning
confidence: 98%
“…reviewed the published work and reported that only 44 cases of malignant transformation of adenomyosis have been documented so far . Furthermore, reported malignant neoplasms originating from cystic adenomyosis are much more rarely available; only one case of clear cell adenocarcinoma arising from a giant cystic adenomyosis, and only one case of endometrioid adenocarcinoma arising from cystic adenomyosis have been documented to date. Other types of malignant transformation of cystic adenomyosis have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Rolly published the first report in 1897 (55). In our review, to date, 44 cases of malignant tumors arising from adenomyosis have been documented (48,51,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Malignant Transformation Of Adenomyosismentioning
confidence: 99%